Differences in health-related quality of life among patients after ankle injury - Gribble, Phillip A.; Kleis, Rachel E.; Simon, Janet E.; Vela, Luzita I.; Thomas, Abbey C. (Frontiers in Sports and Active Living, 2022)
Ankle sprains are the most common injuries sustained in the physically active, often associated with pain and functional limitations long after initial recovery. In recent years, the impact of ankle sprains on general health and health-related quality of life (HRQoL) has been noted in athletes, but is not well-documented in the general population. We examined differences in HRQoL and general health between individuals with ankle sprain history and healthy controls. Those with ankle sprain reported significantly higher body mass index and general body pain, and lower SF-8 physical component scores than healthy controls. Additionally, there is some indication that physical activity is lower in those with ankle sprain history. This is an important step in illustrating the adverse sequelae of ankle sprains on population health and HRQoL.